An octadentate bis(semicarbazone) macrocycle: a potential chelator for lead and bismuth radiopharmaceuticals. Issue 42 (20th October 2020) - Lange, Jaclyn L.; Davey, Patrick R. W. J.; Ma, Michelle T.; White, Jonathan M.; Morgenstern, Alfred; Bruchertseifer, Frank; Blower, Philip J.; Paterson, Brett M.
Abstract : A cyclen bearing semicarbazone pendant groups forms complexes with Bi 3+ and Pb 2+ and was radiolabeled with the alpha-emitting radioisotope 213 Bi. Abstract : A variant of 1, 4, 7, 10-tetraazacyclododecane (cyclen) bearing two semicarbazone pendant groups has been prepared. The octadentate ligand forms complexes with Bi 3+ and Pb 2+ . X-ray crystallography showed that the neutral ligand provides an eight-coordinate environment for both metal ions and intermolecular hydrogen bond interactions have influenced the coordination environments of both complexes in the solid state. NMR spectroscopy revealed a fluxional environment for both complexes. The ligand was radiolabeled with the α-emitting radioactive isotope 213 Bi 3+, which is used in systemic targeted radiotherapy. The resulting complex was stable in serum for at least 90 min (two decay half-lives). The Pb 2+ complex has reasonably fast kinetics of formation ( t 1/2 = 20 min) at 25 °C and pH 7.4. The Bi 3+ and Pb 2+ complexes show kinetic stability in 1.2 M HCl (half-lives of 214 min and 47 min, respectively). This is the first description of a macrocycle bearing semicarbazone pendant groups and its utility in coordinating main group metals, specifically those with radiotherapeutic potential.